Accountability Demands and the Auditor’s Evidence Search Strategy: The Influence of Reviewer Preferences and the Nature of the Response (Belief vs. Action) - Turner, Cynthia Williams (Journal of Accounting Research, 2001)
This study examines differences in auditors’ search behaviors associated with the preferences of audit management (reviewer preferences) and the nature of the required response (belief versus action) in the context of an accounts receivable collectibility review. I find that auditors facing reviewers who expressed concern about auditors spending time specifically looking for evidence inconsistent with explanations provided by the client (credence preference) examined fewer evidence items and followed a more client‐prompted search (i.e., a search for evidence that follows directly from the client’s explanation) than those facing reviewers who expressed concern about auditors’ ready acceptance of client explanations without adequate justification (skepticism preference) and those facing reviewers who expressed no specific concern (unknown preference). Further, auditors in the action conditions examined fewer evidence items and spent less time per evidence item than those in the judgment conditions. Additional analyses also indicate that auditors who were held accountable to a reviewer with an unknown preference generally responded as if the reviewer maintained a skepticism preference.